2021
DOI: 10.3389/fphar.2021.649820
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Polyherbal Formulation, Harak Formula, on UVA-Induced Photoaging of Human Dermal Fibroblasts and Mouse Skin via Promoting Nrf2-Regulated Antioxidant Defense

Abstract: Polyherbal formulation combining multiple herbs is suggested to achieve enhanced therapeutic effects and reduce toxicity. Harak herbal formula (HRF) extracts were proposed to regulate skin responses to UVR through their ability to suppress UVA-induced matrix metalloproteinase-1 (MMP-1) and pigmentation via promoting antioxidant defenses in in vitro models. Therefore, natural products targeting Nrf2 (nuclear factor erythroid 2-related factor 2)-regulated antioxidant response might represent promising anti-photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…Furthermore, the analysis of proteome profiles revealed that rutin treatment caused an induction of proteins involved in the antioxidant defenses and a reduction of proteins involved in the degradation of Nrf2 in UVB-irradiated dermal fibroblasts ( Gegotek et al, 2018 ). Hesperidin, (hesperetin-7-rutinoside), and its aglycone, hesperetin, mostly found in citrus fruits and botanical drugs, have been demonstrated to provide in vitro and in vivo anti-photoaging effects on the skin via stimulating collagen synthesis in association with the antioxidant properties ( Lohakul et al, 2021a ). Citrus sinensis peel extract containing hesperidin loaded lipid nanoparticles showed photoprotective effects on UVR-mediated induction of MMP-1 via JNK signaling, reduction of collagen accompanied by decreased SOD protein production as well as stimulated inflammatory markers (COX-2, prostaglandin E2) and lipid oxidation product, malondialdehyde (MDA), in mouse skin ( Amer et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the analysis of proteome profiles revealed that rutin treatment caused an induction of proteins involved in the antioxidant defenses and a reduction of proteins involved in the degradation of Nrf2 in UVB-irradiated dermal fibroblasts ( Gegotek et al, 2018 ). Hesperidin, (hesperetin-7-rutinoside), and its aglycone, hesperetin, mostly found in citrus fruits and botanical drugs, have been demonstrated to provide in vitro and in vivo anti-photoaging effects on the skin via stimulating collagen synthesis in association with the antioxidant properties ( Lohakul et al, 2021a ). Citrus sinensis peel extract containing hesperidin loaded lipid nanoparticles showed photoprotective effects on UVR-mediated induction of MMP-1 via JNK signaling, reduction of collagen accompanied by decreased SOD protein production as well as stimulated inflammatory markers (COX-2, prostaglandin E2) and lipid oxidation product, malondialdehyde (MDA), in mouse skin ( Amer et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a clinical trial showed that a 12-week topical application of a serum containing 0.1% hesperetin significantly promoted skin hydration and elasticity via enhancing the synthesis of hyaluronic acid ( Sheen et al, 2021 ). Moreover, hesperetin and polyherbal formula extracts containing hesperetin topically applied to mouse skin before UVA exposure three times per week for 2 weeks (a total dose of 60 J/cm 2 ) significantly attenuated MMP-1 upregulation and collagen depletion concomitant with promoting Nrf2 activity and the level of its target proteins (GST and NQO-1) as well as reducing 8-hydroxy-2′-deoxyguanosine (8-OHdG), a product of oxidatively damaged DNA damage, in irradiated mouse skin ( Lohakul et al, 2021a ). Grape fruit stem extract from Muscat Bailey A containing catechin, epicatechin and trans-resveratrol showed protective effects on UVB-induced destruction of collagen fiber through reduction of MMP-1 expression in association with a decrease in lipid peroxidation and restoration of GSH levels in mouse skin ( Cho et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The group of the flavanones have the C ring saturated and also are named dihydroflavones because the only difference with the flavones is that the double bond between positions 2 and 3 is saturated [ 49 ]. In 2021, Lohakul et al [ 82 ] reported that hesperetin pre-administration (2.5, 5, or 10 μg/mL) in UVA-irradiated HDFs decreased ROS generation and also reduced collagen depletion and MMP-1 activity. Additionally, this flavonoid positively regulated Nrf2 activity and its genes NAD(P)H: quinone oxidoreductase 1 (NQO-1) and glutathione S-transferase (GST) ( Table 3 ).…”
Section: Anti-photoaging and Photoprotective Properties Of Flavonoidsmentioning
confidence: 99%
“…Furthermore, this flavonoid increased nuclear Nrf2 levels and its NQO-1 and GST target proteins. Additionally, the hesperetin decreased the 8-OHdG, an indicator of oxidative DNA damage, in mice skin, indicating an attenuation of photoaging through the ability of hesperetin to positively regulate Nrf2; therefore, this flavonoid could be a promising agent to restore redox equilibrium and help in treatment against skin photoaging [ 82 ].…”
Section: Anti-photoaging and Photoprotective Properties Of Flavonoidsmentioning
confidence: 99%
“…It is widely grown in India, Malaysia, and Thailand. In Thai traditional medicine, its leaves and roots are used in the treatment of fever, inflammation, skin diseases, and asthma [ 15 , 16 ]. In addition, C. petasites has generally been used in formulations of some multi-herb medicinal recipes such as the traditional formula “Ha-Rak” remedy (also known as Ben-Cha-Lo-Ka-Wi-Chian).…”
Section: Introductionmentioning
confidence: 99%